Belis dan Perilaku Memilih Perempuan di Kabupaten Nagekeo, Flores, Nusa Tenggara Timur - Dwiganura Apu (Universitas Medan Area, 2021)
This paper aims to examine the relationship between marriage / marriage with the belis system (dowry /dowry) and obedience (wife) to the husband, and whether these two factors influence women's voting behavior in the general election in Nagekeo. . Marriage by giving a belis that is felt to be of high economic value demands the wife's level of compliance with her husband, because with the granting of belis, the husband feels he has full power over women to approach this problem using the theoretical reference from the concept of Gender and Development, thus knowing the extent to which women are involved in determining their own choices, not only in a wider scope, but in a small scope within the family as well. Data collected through in-depth interviews with informants, and analyzed qualitatively. This study concludes that belis here is a cultural heritage contained with historical and social values in it. However, the belis did not have a full effect on the level of compliance and voting behavior of women in the elections in Nagekeo.